"No One is Poor in Himachal": Cultivating Stateless Agency in an Indian Village Assembly. (15th April 2021) - Carlan, Hannah
Abstract : This article examines the bedrock of rural governance in India—the village assembly, or gram sabha —and the deliberative process whereby citizens are designated as "below the poverty line" (BPL). I examine one gram sabha in Himachal Pradesh wherein BPL status was eradicated altogether, leaving hundreds of people ineligible for a vast array of state aid programs. I argue that this outcome relied on an interactional achievement whereby state actors (bureaucrats and elected representatives) rendered village residents into a collectivized agent while erasing their own role and responsibility from the proceedings. These semiotic processes of collectivization and erasure underlie what I call "stateless agency." I trace three linguistic resources that cultivate stateless agency: (i) causative verbs that distribute agency across multiple grammatically encoded participant roles; (ii) code switches from the local language, Kangri, into a register of English‐infused Hindi that invokes what I call the "bureaucratic voice"; and (iii) metapragmatic statements that explicitly attribute agency to other speaker(s). This investigation builds on studies of grammar and political agency (Duranti 1990; 1994) and bureaucratic agency (Hull 2003; 2012) by demonstrating how linguistic resources mediate the paradoxical erasure of state actors from bureaucratic and democratic practice, with often drastic consequences for rural livelihoods.